Does Banking Efficiency, Regulation, and Operations Affect Banking Performance in South Asia: Dynamic Correlated Model Approach - Syed, Aamir Aijaz (Frontiers in Applied Mathematics and Statistics, 2020)
This study intends to find out how the bank or industry-specific variables like banking regulation, banking efficiency, and banking operations affect nonperforming loans in South Asia. To achieve this objective this study has employed robust 1st and 2nd generation Unit root tests, CIPS test, PMG and Dynamic Correlated Model approach on the panel data set of selected South Asian countries from 1995-2019, to avoid the implications of Cross-sectional dependency on the result analysis. The finding of the study shows that loose banking operations, lower exchange rate, and volatile interest rate have a significant positive relationship with nonperforming loan whereas lower banking efficiency have a significant negative relationship with nonperforming loans. The study also confirms the importance of cross-sectional dependencies in getting more accurate and robust results. This study will be useful for policy implementation and to understand the importance of micro banking variables in controlling nonperforming loans, apart from contributing toward the literature of cross-sectional dependency.